Effects of Repetitive Hyperbaric Oxygen Treatment in Patients with Acute Cerebral Infarction: A Pilot Study - Cheng-Hsin Chen; Shao-Yuan Chen; Vinchi Wang; Chao-Ching Chen; Kaw-Chen Wang; Chih-Hao Chen; Yi-Chien Liu; Kuo-Cheng Lu; Ping-Keung Yip; Wen-Ya Ma; Chuan-Chieh Liu (The Scientific World Journal)
The role of hyperbaric oxygen therapy (HBOT) in the treatment of acute ischemic stroke is controversial. This prospective study assessed the efficacy and safety of HBOT as adjuvant treatment on 46 acute ischemic stroke in patients who did not receive thrombolytic therapy. The HBOT group (n=16) received conventional medical treatment with 10 sessions of adjunctive HBOT within 3–5 days after stroke onset, while the control group (n=30) received the same treatment but without HBOT. Early (around two weeks after onset) and late (one month after onset) outcomes (National Institutes of Health Stroke Scale, NIHSS scores) and efficacy (changes of NIHSS scores) of HBOT were evaluated. The baseline clinical characteristics were similar in both groups. Both early and late outcomes of the HBOT group showed significant difference (P≤0.001). In the control group, there was only significant difference in early outcome (P=0.004). For early efficacy, there was no difference when comparing changes of NIHSS scores between the two groups (P=0.140) but there was statistically significant difference when comparing changes of NIHSS scores at one month (P≤0.001). The HBOT used in this study may be effective for patients with acute ischemic stroke and is a safe and harmless adjunctive treatment.